Creating a Rich Learning Environment for Remote Postgraduate Learners - Lonie, Anne-Louise; Andrews, Trish (Australian and International Journal of Rural Education, 2009)
At Rangelands Australia, a centre in the School of Natural and Rural Systems Management at the University of Queensland, we have recently trialled virtual classroom technology for the delivery of postgraduate support courses. We wanted to explore the capacity of this learning modality to provide collaborative, interactive, synchronous learning environments for our target market—geographically isolated, rural students whose access to rich learning environments was limited by distance. We found that the virtual classroom platforms had considerable capacity to enhance the learning experiences of remote students while achieving the desired learning outcomes. However, we noted the demands and challenges that managing a virtual classroom placed on the facilitator, involving roles and responsibilities which are likely to be unfamiliar. We concluded that, if the facilitator is technically and pedagogically prepared for the virtual classroom platform, this learning approach can realistically provide an active and collaborative learning experience for geographically remote students.